Environmentalist Predispositions and Recycled Product Preferences - BULUT, Cağrı; NAZLI, Murat (International Journal of Contemporary Economics and Administrative Sciences, 2020)
The study aims to uncover “environmentalist predispositions” based on the Big Five Personality with support of the theory of planned behavior and examines the effects of environmentalists’ predispositions on the recycled product preferences. Based on the big five personality traits, this paper proposes a typology on the environmentalists’ predispositions for conscious consumption studies, which consists of concern, pleasure, consciousness, beliefs, and norms. The method of the empirical study is a self-reported survey with a sample of 256 participants from a developing economy. The results of the factor analyses confirm the five-dimensional theoretical construct of individuals’ predispositions towards environmentalism. Furthermore, multiple regression analyses for testing the associations of the environmentalist predispositions on recycled product preferences disclose that among five of the dimensions, environmentalist consciousness, environmentalist beliefs, and environmentalist norms have joint effects on preferring a recycled product. This study is one of the preliminary attempts that examines the effects of environmentalist predispositions on a conscious consumption choice, specifically on preferring the recycled products, as a green purchasing behavior type.